Promotif kesehatan melalui edukasi Keluarga Berencana (KB) - Sitti Fatimah; Musni Musni; Desi Heriyana (Indonesian Public Health-Observer Information Forum (IPHORR) Kerja sama dengan: Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2026)
Background: Family planning (FP) is an effort undertaken by married couples to regulate the number, spacing, and timing of their children through the use of contraceptive methods to create a healthy, prosperous, and quality family. According to the World Health Organization (WHO), family planning is an action that enables individuals and couples to anticipate and achieve the desired number of children and determine the spacing and timing of births through the use of safe and effective contraceptive methods. The Family Planning (FP) program is not merely an effort to regulate the number of children, but rather a preventive health strategy proven to reduce maternal and infant mortality, improve the quality of family life, and support sustainable development. Family planning education shifts the societal paradigm from